Brovchenko Т. О., Korolova Т. М. English Phonetics: Contrastive analysis of English and Ukrainian Pronunciation - Калита, A. (Мовознавство, 2008)
Рецензія на книгу: Brovchenko Т. О., Korolova Т. М. English Phonetics: Contrastive analysis of English and Ukrainian Pronunciation. Миколаїв : МДГУ ім. Петра Могили, 2006.— 2-е вид. випр. і доп.— 296 с.